THE ROLE OF PUBLIC POLICIES IN THE ACTIVATION OF THE EMPLOYMENT POLICY IN ALGERIA - Chelil Abdellatif; Benazza Mohammed (European Scientific Journal, ESJ, 2014)
At the beginning of the third millennium, Algeria experienced a different developmental policy through the programs of economic recovery and growth support, helped by the increase in oil prices. This affected the situation of work, where unemployment rates fall relatively in this period compared with the previous one, but critics said that it was not as was expected.